2020
DOI: 10.2147/dddt.s259228
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>Clostridium histolyticum</em> (AA4500) for the Treatment of Adhesive Capsulitis of the Shoulder: A Randomised Double-Blind, Placebo-Controlled Study for the Safety and Efficacy of Collagenase – Single Site Report</p>

Abstract: Background/Hypothesis: Adhesive capsulitis of the shoulder results in pain and restricted movement of the glenohumeral joint. Hypothesis: There would be a difference in active range of movement in the affected shoulder of patients with adhesive capsulitis after receiving a series of injections of collagenase Clostridium histolyticum (CCH) compared to placebo. Methods: This study reports the results from a single site that was part of a 321-participant, multicenter, double-blind, prospective parallel-group, ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Some animal studies have performed collagenase injection to treat SS, which resulted in good outcomes [ [51] , [52] , [53] ]. However, as collagen is an indispensable part of the extracellular matrix, it is not clear whether collagenase could be utilized in clinical practice or not [ 54 ]. Alternatively, we proved the possibility of collagen secretion inhibition by BMSC-EVs, of which the effect relied on TGF-β/Smad signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Some animal studies have performed collagenase injection to treat SS, which resulted in good outcomes [ [51] , [52] , [53] ]. However, as collagen is an indispensable part of the extracellular matrix, it is not clear whether collagenase could be utilized in clinical practice or not [ 54 ]. Alternatively, we proved the possibility of collagen secretion inhibition by BMSC-EVs, of which the effect relied on TGF-β/Smad signaling.…”
Section: Discussionmentioning
confidence: 99%
“…CCH is typically given in a series of 3 injections over 6 weeks. A randomized study showed improvement in subjective function with CCH but no notable increase in ROM compared with placebo 151 . Another study found a greater improvement in ROM at 3 months with CCH than with exercise therapy alone 143 .…”
Section: [H3] Alternative Interventionsmentioning
confidence: 99%
“…While CCH has shown relative safety and efficacy, it can trigger the production of neutralizing antibodies in patients [ 47 ]. Additionally, AA4500 has proven ineffective in treating other fibrotic conditions, such as adhesive capsulitis of the shoulder [ 48 ]. Potential future applications abound.…”
Section: Direct Targetingmentioning
confidence: 99%